1989
DOI: 10.1007/bf02398244
|View full text |Cite
|
Sign up to set email alerts
|

So-called “Co-Mo-S” phase observed in carbon-supported Co and Co-Mo sulfide catalysts by Mössbauer emission spectroscopy

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It seemed unlikely that the surface-oxide phase should remain nearly unaffected by such a treatment in H,S/H,, while already at room temperature iron sulfides are formed in these catalysts [ 91. Furthermore, recently Van der Kraan et al [30,31] have reported a similar quadrupole splitting as ascribed to the "CO-MO-S" phase by Topsare et al…”
Section: Comparison Of Alumina-supported Fe and Fe-mo Catalystsmentioning
confidence: 65%
“…It seemed unlikely that the surface-oxide phase should remain nearly unaffected by such a treatment in H,S/H,, while already at room temperature iron sulfides are formed in these catalysts [ 91. Furthermore, recently Van der Kraan et al [30,31] have reported a similar quadrupole splitting as ascribed to the "CO-MO-S" phase by Topsare et al…”
Section: Comparison Of Alumina-supported Fe and Fe-mo Catalystsmentioning
confidence: 65%
“…Based on the MES and XAFS studies of supported CoMo catalysts, Crajé et al [31,35,36] and van der Kraan et al [37] proposed a sophisticated surface model of the catalysts, in which highly dispersed Co sulfide particles are located at the edge positions of MoS 2 crystallites and the size of the Co sulfide particles decreases as the Co/Mo ratio decreases. The blocking of the edges of MoS 2 particles by Co sulfide clusters can be easily explained by their surface model.…”
Section: Blocking Of Active Sites By Co Sulfide Clustersmentioning
confidence: 99%
“…The blocking mechanism has been previously proposed to explain lower HDS activities of Co−Mo/Al 2 O 3 impregnation catalysts compared to the activity of Co/MoAl . On the basis of Mössbauer emission spectroscopy and XAFS studies of supported Co−Mo catalysts, Crajé et al and van der Kraan et al proposed that small cobalt sulfide clusters in contact with the edges of MoS 2 particles generate catalytic synergies between cobalt and molybdenum sulfides. However, it appears that the present and previous activity results can be simply explained by blocking of the MoS 2 edge sites and, accordingly, the Co−Mo−S structure by cobalt sulfide clusters.…”
Section: Discussionmentioning
confidence: 99%